2011
DOI: 10.1167/iovs.10-6520
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Angiopoietic Cells and Diabetic Retinopathy in Type 2 Diabetes Mellitus, with or without Macrovascular Disease

Abstract: The circulating angiopoietic CPCs, EPCs, and matEPCs in T2DM patients with DR had a different regulations, with increasing relative differences occurring in proliferative DR, apparently depending on the macrovascular comorbidities. Patients with MVD showed a strong retinopathy-stage-dependent depletion of all angiopoietic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Indeed, it has been recently demonstrated that EPCs from normal but not diabetic patients contribute to postischemic revascularization. 4 Diabetic EPCs are both lower in number 5 and dysfunctional, displaying a shift toward a proinflammatory phenotype. 15 Normal adult and/or FPCs (i) can differentiate into several cell types and (ii) have stimulatory effects on biological processes and are therefore likely to be beneficial for chronic wound patients and those with impaired perfusion.…”
Section: Relevance To Clinical Carementioning
confidence: 99%
“…Indeed, it has been recently demonstrated that EPCs from normal but not diabetic patients contribute to postischemic revascularization. 4 Diabetic EPCs are both lower in number 5 and dysfunctional, displaying a shift toward a proinflammatory phenotype. 15 Normal adult and/or FPCs (i) can differentiate into several cell types and (ii) have stimulatory effects on biological processes and are therefore likely to be beneficial for chronic wound patients and those with impaired perfusion.…”
Section: Relevance To Clinical Carementioning
confidence: 99%
“…In addition, circulating EPCs of T1DM patients with PDR were reported to have increased clonogenic potential (Asnaghi et al, 2006). In T2DM patients with DR, circulating angiopoietic cells as EPCs, and mature EPCs had different regulations in PDR depending on each individual's macrovascular comorbidities (Brunner et al, 2011). Recent findings in diabetic patients have corroborated gathered experimental data, demonstrating that BMderived CD133+ EPCs, as well as, CD14+ monocytes could be mobilized to diabetic epiretinal membranes, contributing to vasculogenesis in PDR (Abu El-Asrar et al, 2011).…”
Section: Epcs and Diabetic Retinopathy (Dr)mentioning
confidence: 78%
“…Additionally, a strong correlation between these neurotrophins and EPC levels in DR patients was found, suggesting that retinal ischemia serves as a signal to stimulate BM-EPCs through selected strong neurotrophic factors that are released into the systemic circulation. Recently, two reports conveyed more important information on the role of different www.intechopen.com progenitor cells in various stages of DR in T1DM and T2DM patients (Brunner et al, 2009(Brunner et al, , 2011. In T1DM, it was demonstrated that in non-PDR patients there was a reduction in circulating EPCs, and that in PDR there was a dramatic increase of mature EPCs (Brunner et al, 2009).…”
Section: Epcs and Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…In some series, diabetes has been associated with the same coronary risk as established coronary disease thereby making it a "coronary artery disease risk-equivalent" (Haffner, Lehto et al 1998). Diabetics without manifest cardiovascular disease have decreased EPC numbers compared to age-matched controls (Tepper, Galiano et al 2002) and diabetics with manifest macrovascular disease such as CAD, peripheral vascular disease or stroke have further reduced EPC numbers (Fadini, Miorin et al 2005;Brunner, Hoellerl et al 2011). Further, EPCs in diabetics are dysfunctional when compared to EPCs from non-diabetic subjects.…”
Section: Insulin Resistance the Metabolic Syndrome And Diabetesmentioning
confidence: 99%